Estudos categorizados como awaiting classification em revisões sistemáticas Cochrane: frequência, justificativas e adequação às recomendações do Cochrane Handbook - Pacheco, Rafael Leite [UNIFESP] (2019)
Objectives: To identify the reasons for considering a study as an “awaiting classification study” (ACS) in Cochrane reviews and to propose a guidance for management and reporting the decision for encoding a study as an ACS. Study Design and Setting: A cross-sectional analysis of Cochrane reviews, conducted in the Universidade Federal de São Paulo (UNIFESP), Brazil. Methods: All Cochrane systematic reviews of interventions published in the issues 1 to 6/2019 of the Cochrane Library were assessed. The reviews were manually identified in the Cochrane Library website and its references were manually extracted by two independent authors and organized in a pre-established form. Disagreements in the selection and extraction process were solved by consulting a third researcher. The justifications to consider the classified studies as ACS were distributed in 13 distinct categories. Results: We included 260 Cochrane reviews that classify the study 426 as ACS. The categories more frequently observed to classify the study as ACS were: no sufficient information to include or to exclude (111, 26.06%), justification not reported/not clear (82, 19.25%), study completed but without published results (64, 15.02%) and full text unavailable (62, 14,56%). Other alleged reasons were more infrequent. A guide for authors, reviewers and editors of systematic reviews was proposed to facilitate and make the process of classification more transparent. A checklist was also proposed and may be useful to manage and report ACS in future reviews. We suggested reasons for considering a study an ACS and proposed a checklist that may be useful to proper manage and report ACS in future reviews. Conclusion: The findings of this study showed that the main justification to categorize the studies as ACS were often inadequate or underreported by the review authors. This can be considered a shortcoming that compromise the transparency, reliability and reproducibility of Cochrane reviews. The adoption of a standardized checklist may be an initial strategy to improve this scenario. Future actions are warranted to better understand the impact of ACS in Cochrane systematic reviews and other systematic reviews.